Methodological Reporting Quality of Randomized Controlled Trials in 3 Leading Diabetes Journals From 2011 to 2013 Following CONSORT Statement. Issue 27 (July 2015) - Zhai, Xiao; Wang, Yiran; Mu, Qingchun; Chen, Xiao; Huang, Qin; Wang, Qijin; Li, Ming; Suarez., Alejandro Lopez
<x xml:space="preserve">Abstract</x> Abstract To appraise the current reporting methodological quality of randomized clinical trials (RCTs) in 3 leading diabetes journals. We systematically searched the literature for RCTs in Diabetes Care, Diabetes and Diabetologia from 2011 to 2013. Characteristics were extracted based on Consolidated Standards of Reporting Trials (CONSORT) statement. Generation of allocation, concealment of allocation, intention-to-treat (ITT) analysis and handling of dropouts were defined as primary outcome and "low risk of bias." Sample size calculation, type of intervention, country, number of patients, funding source were also revealed and descriptively reported. Trials were compared among journals, study years, and other characters. A total of 305 RCTs were enrolled in this study. One hundred eight (35.4%) trials reported adequate generation of allocation, 87 (28.5%) trials reported adequate concealment of allocation, 53 (23.8%) trials used ITT analysis, and 130 (58.3%) trials were adequate in handling of dropouts. Only 15 (4.9%) were "low risk of bias" trials. Studies at a large scale (n > 100) or from European presented with more "low risk of bias" trials than those at a small scale (n ⩽ 100) or from other regions. No improvements were found in these 3 years. This study shows that methodological reporting quality of RCTs in the major diabetes journals remains suboptimal. It can be further improved to meet and keep up with the standards of the CONSORT statement.